Validity of household dietary diversity score as a measure of food insecurity among households in Lucena City, Quezon - Arias, Frances Pola S. (2017.)
Food security is a multifaceted issue experienced by nations, globally. A trend currently being explored in recent studies in measuring food security is the Dietary Diversity Score (DDS). DDS is a qualitative measurment of food security which consists of simple counts of food groups that a household or an individual has consumed over the preceding 24 hours. Individual Dietary Diversity Score (IDDS), which is one of the two types of DDS measured at the individual level, is considered a proxy for nutrient adequacy of the diet of individuals. On the other hand, Household Dietary Diversity Score (HDDS), which is another type of DDS, obtains a snapshot of the economic ability of a household, making it an effective indicator of food insecurity. To assess the validity of the HDDS as a tool for measuring food insecurity, HFIAS and Household Mean Adequacy Ratio (HHMAR) were used as reference standards. HFIAS and HHMAR are two of the most frequently used methods in measuring household food insecurity. HFIAS is obtained by using a standardized questionnaire which consists of a list of security-related conditions which had occurred in the last thirty day while the HHMAR is obtained by performing a household 24-hour food recall. The HHMAR for each household is calculated as the average of the energy adequacy ration and the seven micronutrients. Using HFIAS and HHMAR, at least 70% of the selected households in Lucena City were found to be food insecure, while the mean HDDS obtained is 6.5 (HDDS 12 as the highest). Comparing the urban and rural barangays, the mean HDDS and HDDS distribution of Iba. Iyam (urban) and Dalahican (rural) were significantly different from each other (P, 0.001; 95% CI). Spearman correlation and Receiver Operating Curve Analysis (ROC) performed between HDDS and the reference standards indicated that HDDS is a fair indicator of food insecurity. HDDS showed a positive correlation with HHMAR (r = 0.43, p<0.001) and a negative correlation with HFIAS (r = -0.347, p<0.001). The ROC Analysis was done to determine the appropriate HDDS cut-off for identifying food insecure households using the HFIAS and HHMAR as reference standards. The for levels of food security of HFIAS were reclassified into HFIAS Group 1 (food secure & mildly food insecure vs. moderately & severely food insecure) and HFIAS Group 2 (food secure vs. mildly, moderately, & severely food insecure)....
Available in CD, pdf copy.
Thesis (Master of Science in Public Health, Nutrition)--University of the Philippines Manila.
Keywords: Food insecurity; Dietary Diversity Score (DDS).